Asymmetric synthesis of (-)-(R)-sitagliptin - Davies, S; Fletcher, A; Lv, L; Roberts, P; Thomson, J (2012)
The asymmetric synthesis of (-)-(R)-sitagliptin was achieved in seven steps from commercially available starting materials using the highly diastereoselective conjugate additions of either lithium (R)-N-benzyl-N- (α-methylbenzyl)amide or lithium (R)-N-benzyl-N-(α-methyl-p- methoxybenzyl)amide to tert-butyl 4-(2′,4′,5′-trifluorophenyl) but-2-enoate to install the correct stereochemistry. Subsequent sequential acid-catalysed hydrolysis of the resultant β-amino esters, HOBt/EDC mediated coupling with the triazolopyrazine fragment, and hydrogenolysis gave (-)-(R)-sitagliptin in 43% and 42% overall yields, respectively. © 2012 Elsevier Ltd. All rights reserved.